El trabajo infantil y sus consecuencias socio jurídicas en la ciudad de Ibarra, estudio de casos relevantes - Cadena Salazar, Kevin Israel (2023)
Child labor is an activity that limits the comprehensive development of children and adolescents based on the fact that they are part of vulnerable groups. Therefore, it is essential to consider the set of rights that are being violated. The International Labor Organization defines said activity as 'All work that deprives children of their childhood, their potential and their dignity, and that is detrimental to their physical and psychological development' therefore child labor affects the right of boys, girls and adolescents to carry out activities appropriate to their age and that allow and encourage the development of their intellect, potentialities and capacities. The reason for the existence of child labor arises from the lack of economic resources in the homes, which forces children to seek a daily livelihood in order to contribute to the economy of their families. However, as has been said, child labor hinders access to education, and above all hinders the comprehensive development of children, especially in the city of Ibarra. Therefore, it is considered a problem because child labor is an illegal activity that violates rights and limits the comprehensive development of children. Despite the existence of laws and international treaties that guarantee these rights, it has been possible to observe the violation of these rights.